K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 8 2017

\(P+\left(x^2-2y^2\right)=x^2-y^2+3y^2-1\)

\(P+x^2-2y^2=x^2+2y^2-1\)

\(P=x^2+2y^2-1-x^2+2y^2\)

\(P=4y^2-1\)

\(P=\left(2y-1\right)\left(2y+1\right)\)

nho nha

26 tháng 8 2017

Suy ra P=x^2-y^2+3y^2-1-(x^2-2y^2)

Suy ra P= x^2 - y^2+3y^2-1-x^2+2y^2

Suy ra P=(x^2-x^2)+(-y^2+3y^2+2y^2)-1

Suy ra P= 4y^2-1

25 tháng 3 2018

a) P + (x2 – 2y2) = x2 – y2 + 3y2 – 1

P = (x2 – y2 + 3y2 – 1) - (x2 – 2y2

P = x2 – y2 + 3y2 – 1 - x2 + 2y2

P = x2 – x2 – y2 + 3y2 + 2y2 – 1

P = 4y2 – 1.

Vậy P = 4y2 – 1.

b)  Q – (5x2 – xyz) = xy + 2x2 – 3xyz + 5

Q = (xy + 2x2 – 3xyz + 5) + (5x2 – xyz)

Q = xy + 2x2 – 3xyz + 5 + 5x2 – xyz

Q = 7x2 – 4xyz + xy + 5

Vậy Q = 7x2 – 4xyz + xy + 5.

25 tháng 1 2016

P=4y2-1

Q=xy+7y2-4xyz+5

21 tháng 3 2017

a) \(P+\left(x^2-2y^2\right)=x^2-y^2+3y^2-1\)

\(\Rightarrow P=\left(x^2-y^2+3y^2-1\right)-\left(x^2-2y^2\right)\)

\(\Rightarrow P=x^2-y^2+3y^2-1-x^2+2y^2\)

\(\Rightarrow P=\left(x^2-x^2\right)-\left(y^2-3y^2-2y^2\right)-1\)

\(\Rightarrow P=4y^2-1\)

Vậy đa thức \(P\)\(4y^2-1\).